Model Epidemi Seir dengan Insidensi Standar - Roni Tri Putra (Jurnal Ilmiah Poli Rekayasa, 2016)
In this paper, it will be studied stability for a SEIR epidemic model with infectious force in latent, infected and immune period with standard incidence. From the model it will be found investigated the existence and uniqueness solution  of points its equilibrium. Existence solution of points equilibrium proved by show its differential equations system of equilibrium continue, and uniqueness solution of points equilibrium proved by show its differential equation system of equilibrium differentiable continue.